2000
DOI: 10.1136/oem.57.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural effects of occupational exposure to cadmium: a cross sectional epidemiological study

Abstract: Background-A patient with unexplained minor behavioural changes associated with an axonal sensorimotor polyneuropathy had a history of chronic occupational exposure to cadmium (Cd). Although animal studies have shown that Cd is a potent neurotoxicant, little is known about its toxicity for the human central nervous system. The aim of this study was to investigate the toxic potential of chronic occupational exposure to Cd on neurobehavioural functions. Methods-A cross sectional epidemiological study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(118 citation statements)
references
References 42 publications
0
112
0
6
Order By: Relevance
“…Foi verificado que podem ocorrer alterações neurológicas em indivíduos expostos ao cádmio, porém com função renal preservada e baixas concentrações do metal nos exames laboratoriais disponíveis 27 . Uma maneira de tentar se assegurar que nenhum indivíduo exposto a agentes possivelmente ototóxicos em concomitância ao ruído, ou mesmo sem este, tenha alteração auditiva, é a realização de testes audiométricos periódicos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Foi verificado que podem ocorrer alterações neurológicas em indivíduos expostos ao cádmio, porém com função renal preservada e baixas concentrações do metal nos exames laboratoriais disponíveis 27 . Uma maneira de tentar se assegurar que nenhum indivíduo exposto a agentes possivelmente ototóxicos em concomitância ao ruído, ou mesmo sem este, tenha alteração auditiva, é a realização de testes audiométricos periódicos.…”
Section: Discussionunclassified
“…Os achados têm sido favoráveis à hipótese do cádmio ter uma participação no desenvolvimento da polineuropatia 26 . 27 . O conhecimento disponível para a compreensão dos aspectos ocupacionais da exposição ao cádmio é ainda fragmentário, muitas vezes sendo necessário fazer inferência a partir de estudos epidemiológicos e em animais.…”
Section: Ruído Exposição a Metais E Alteração Auditivaunclassified
“…In several experimental models, it has been reported that Cd induces oxidative damage in brain mitochondria (Abib et al, 2011;Chen et al, 2011 (Sena and Chandel, 2012). It has been reported that Cd exposure produced long-term impairments of neurobehavioral status such as alterations in attention and memory as well as in the psychomotor and visuomotor functioning and speed in workers (Viaene et al, 2000;Haider et al, 2015).…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Monroe and Halvorsen, 2006 provided evidence that CdCl2 increases oxidative stress in nervous cells. In experimental studies with animals, cadmium can induce neurotoxicity with a wide spectrum of clinical entities including neurological disturbance (Viaene et al, 2000). Changes in the normal neurochemistry of the brain (Gutierrez-Reyes et al, 1998), several authors have shown that antioxidants should be one of the important components of an effective treatment of cadmium poisoning (Valko et al, 2006).…”
Section: Issn: 2320-5407mentioning
confidence: 99%